Re-Thinking Social Capital - Zlatko Bukač ([sic])
The concept of social capital has been used very often in sociological researches over the last two decades. Measuring social capital in civil society, neighborhoods and educational systems is merely a part of its popular usage. Many sociologists tend to use the concept of social capital very freely and therefore expand the definition of social capital. The author’s personal experience indicates that there have been a great number of academic discussions, research planning and public speeches implementing the notion of social capital without taking a detailed consideration of what that concept truly entails. By overviewing the available literature on social capital, it is actually no wonder that both sociologists and the noted concept were in this confusing situation. As Field stated in his book Social Capital (Key Ideas), published in 2008, his work was “the first attempt to provide an extended introduction on increasingly influential concept of social capital” (Field 1). Quibria notes that even though there is a vast number of research conducted on social capital in many academic fields and with various approaches ‘the concept of social capital remains largely elusive’’(1). That obviously is not an obstacle because there is a constantly growing interest in social capital. A vast body of research concerning, measuring, and defining social capital is available today, which helps a researcher to analyze and compare all of the perspectives concerning social capital. This can be of great importance when researchers approach a somewhat new subject of research such as online communication and, more specifically, online games.